Tuberculosis of the gastrointestinal tract and associated viscera. (August 2018) - Malikowski, Thomas; Mahmood, Maryam; Smyrk, Thomas; Raffals, Laura; Nehra, Vandana
Abstract: Tuberculosis involvement of the gastrointestinal tract, peritoneum, and associated viscera is an uncommon but well described entity. While peritoneal tuberculosis and tuberculous enteritis are more common, involvement of the esophagus, stomach, colon, rectum, anus, liver, bile ducts, gallbladder, and pancreas can occur. Diagnosis is challenging as cases often mimic neoplasm or inflammatory bowel disease. In this review we outline the pathogenesis, clinical presentation, diagnostic testing, and treatment strategies pertaining to such cases.